Enhancing Regional Competitiveness through Intermodal Logistics: A Case Study of Central Java - Saadi, Terry Devara Tri; Dwicahayaniawan, Agnes Septi (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2025)
Focusing on Central Java, this study presents a regional case study of logistics route optimization. Logistics inefficiency remains a critical bottleneck to regional competitiveness in Indonesia, particularly in provinces like Central Java, where dense population and industrial activity demand high-performing transport systems. This study explores the potential of intermodal logistics (integrating rail and road transport) to reduce distribution costs and enhance supply chain sustainability. Using Dijkstra’s algorithm on a custom-built transport network graph derived from OpenStreetMap data, we simulate logistics costs across 16 districts in Semarang City under two scenarios: direct road transport and intermodal routing via Semarang Tawang Station. The analysis incorporates vehicle capacities, fuel consumption rates, and population-based demand estimates to calculate total delivery costs, revealing that intermodal solutions yield substantial savings in most districts. Statistical testing confirms the significance of these cost differences. Unlike previous studies, this research contributes to the literature by providing a network-level, cost-optimization assessment of logistics modal in a regional context. Key policy recommendations include developing intermodal hubs, upgrading rail access, and tailoring vehicle deployment to local infrastructure constraints. This study not only contributes to the academic discourse on transport optimization and sustainable logistics but also provides actionable insights for planners and decision-makers aiming to enhance regional connectivity and reduce logistics burdens on businesses.